4(x-1)+6=5(2-x)+1
4x-4+6=10-5x+1
4x+2=11-5x
-2 -2
___________
4x=9-5x
+5x +5x
__________
9x=9
/9 /9
_________
x=1
2006-11-06 12:36:59
·
answer #1
·
answered by ... 6
·
0⤊
0⤋
4(x-1) + 6 = 5(2-x) + 1
4x-4+6 = 10-5x+1
4x+2 = 11-5x
9x=9
x=1
2006-11-06 20:34:40
·
answer #2
·
answered by rakshit 2
·
0⤊
0⤋
4(x-1) + 6 = 5(2-x) + 1
4x-4+6 = 10-5x+1
4x+2 = 11-5x
9x=9
x=1
2006-11-06 20:33:14
·
answer #3
·
answered by Latina129 2
·
0⤊
0⤋
4(x-1) + 6 = 5(2-x) + 1
4x - 4 + 6 = 10 - 5x + 1
4x + 2 = 11 - 5x
4x + 5x + 2 = 11
9x + 2 = 11
9x = 11-2
9x = 9
x = 9/9
x = 1
2006-11-07 08:21:12
·
answer #4
·
answered by Akilesh - Internet Undertaker 7
·
0⤊
0⤋
4(x-1)+6=5(2-x)+1
then multiply the 4 and 5 into their quantities
4x-4+6=10-5x+1
combine like terms
4x+2=11-5x
.....add -5x to both sides and subtract 2 to both sides
9x=9
divide by 9
x=1
2006-11-06 20:36:34
·
answer #5
·
answered by kiyomidog 2
·
0⤊
0⤋
4x-4+6=10-5x+1
4x+2=11-5x
9x=9
x=1
2006-11-06 20:34:03
·
answer #6
·
answered by James C 2
·
0⤊
0⤋
4x-4+6=10-5x+1
4x+2=11-5x
9x=9
x=1
2006-11-06 20:33:22
·
answer #7
·
answered by Anonymous
·
0⤊
0⤋
4x - 4+6 =10 - 5x +1
9x = 9
x = 1
2006-11-06 20:36:08
·
answer #8
·
answered by HoneyBunny 7
·
0⤊
0⤋
4(x)+4(-1)+6=5(2)+5(-x)+1
4x-4+6=10-5x+1
4x+2=11-5x
4x-4x+2=11-5x-4x
2=11-9x
2-11=11-11-9x
-9=-9x
(-1/9)(-9)=(-1/9)(-9x)
1=x
x=1
2006-11-06 20:35:03
·
answer #9
·
answered by Anonymous
·
0⤊
0⤋